2016
DOI: 10.4028/www.scientific.net/kem.673.183
|View full text |Cite
|
Sign up to set email alerts
|

Precipitated Silica Derived from Palm Oil Mill Fly Ash: Kinetics and Characterization

Abstract: The silica extraction from palm oil mill fly ash (POMFA) using sodium hydroxide as one of viable processes for obtaining silica from agricultural waste was investigated. The effects of extraction time and temperature were closely examined to study the kinetics of the process. The fixed variables used in the present work were mass of POMFA 468.2 gram; the POMFA mass to NaOH volume ratio 0.2341 g/cm3; the concentration of NaOH 1.4 N and the stirring speed of 1065 RPM. The levels of temperature employed were 348 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 15 publications
4
10
1
Order By: Relevance
“…If it is assumed that the carbon is fixed it can be calculated that of 60.11% silica can be extracted from the POMFA. This is in accordance with Utama et al, (2016) that reported at the similar conditions around 60% of silica can be extracted from POMFA [4].…”
Section: Synthetic Amorphous Silicasupporting
confidence: 82%
See 2 more Smart Citations
“…If it is assumed that the carbon is fixed it can be calculated that of 60.11% silica can be extracted from the POMFA. This is in accordance with Utama et al, (2016) that reported at the similar conditions around 60% of silica can be extracted from POMFA [4].…”
Section: Synthetic Amorphous Silicasupporting
confidence: 82%
“…The alkaline extraction combine with the sol-gel precipitation and mechanical fragmentation was applied to produce precipitated silica, the result was 60% of silica from the ash can be extracted. The silica content in the POMFA was 39% so from 1 ton of POMFA only 234 kg silica can be extracted [4]. The process above still produces waste of 766 kg.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The porous structure observed was mainly due to the high combustion temperature that created holes on the particle's surface, thus, creating a larger surface area on the particles (Yahya et al, 2010). As the temperature reaches up to 700C, more agglomeration into irregular shapes can be seen through images due to mineral content in the crystalline form as the particles become more brittle (Utama et al, 2018;Yang et al, 2022). These results can also be proven through EDX spectra in which the silica intensity increased with the temperature increase.…”
Section: Morphological Analysismentioning
confidence: 83%
“…It can be observed that the particle size is smaller than 500 nm. The spherical clusters displayed in Figure 3f indicate the presence of amorphous silica aggregated due to the increase of pH during the treatment using an alkaline solution (Permatasari et al, 2016;Quercia et al, 2013;Utama et al, 2018). The EDX spectra showed an increase in the intensity of silica.…”
Section: Morphological Analysismentioning
confidence: 95%